Perkembangan Kecerdasan Buatan Dalam Industri Video Game - Izza, Muhammad Gausan; Febria Wardhani, Dyah (Jurnal Sintaks Logika, 2025)
Abstract Artificial Intelligence (AI) has played an increasingly significant role in the video game industry, providing more dynamic and realistic gaming experiences. This research discussed the development of AI in video games, spanning from basic techniques to advanced algorithms. Over the past decades, AI has evolved from simple scripts into systems capable of learning and adapting through machine learning and neural network-based approaches. The application of AI in video games has included enhancing the behavior of non-playable characters (NPCs), optimizing game mechanics, and personalizing user experiences. Furthermore, AI has been utilized in procedural content generation (PCG) to automatically create expansive and diverse game worlds. This article also explored the challenges and future prospects of AI within the gaming industry, encompassing the ethics of AI implementation and its influence on game design. It was concluded that advancements in AI technology are expected to continue to elevate the interactivity and complexity of games, thereby creating more immersive experiences for players.